2009
DOI: 10.1016/j.jasms.2009.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Gas-phase scrambling of disulfide bonds during matrix-assisted laser desorption/ionization mass spectrometry analysis

Abstract: Evidence for photo-induced radical disulfide bond scrambling in the gas phase during matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) is described. The phenomenon was observed during the analysis of tryptic peptides from insulin and was confirmed in the determination of disulfide bonds in the rhamnose-binding lectin SEL24K from the Chinook salmon Oncorhynchus tshawytscha. A possible mechanism for this surprising scrambling is proposed. Despite this finding, the disulfide bond pattern in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…We measured peptide C2 in oxidized form (with intramolecular disulfide bonds) as well as non-reduced insulin (with intermolecular disulfide bonds) in various DHB matrix isomers (see below) with different laser intensity, and we never observed peaks shifted by 2 Da compared to the original oxidized molecules. In our opinion, which is consistent with other references, [10] the answer to the question in the title of this paragraph should be 'No!'. Mass spectra of cysteine-containing peptides modified by Ellman's reagent Mass spectra of the peptide C2 modified by Ellman's reagent (structure C2-TNB 2 ) showed that this modification is not stable under MALDI conditions.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…We measured peptide C2 in oxidized form (with intramolecular disulfide bonds) as well as non-reduced insulin (with intermolecular disulfide bonds) in various DHB matrix isomers (see below) with different laser intensity, and we never observed peaks shifted by 2 Da compared to the original oxidized molecules. In our opinion, which is consistent with other references, [10] the answer to the question in the title of this paragraph should be 'No!'. Mass spectra of cysteine-containing peptides modified by Ellman's reagent Mass spectra of the peptide C2 modified by Ellman's reagent (structure C2-TNB 2 ) showed that this modification is not stable under MALDI conditions.…”
Section: Resultssupporting
confidence: 90%
“…We measured peptide C2 in oxidized form (with intramolecular disulfide bonds) as well as non‐reduced insulin (with intermolecular disulfide bonds) in various DHB matrix isomers (see below) with different laser intensity, and we never observed peaks shifted by 2 Da compared to the original oxidized molecules. In our opinion, which is consistent with other references, the answer to the question in the title of this paragraph should be ‘No!’.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Although the charge state per se may not be important, it is likely for peptide pairs that charge repulsion overcomes any noncovalent interactions that otherwise inhibit dissociation. In the absence of Coulombic repulsion, two peptide radicals generated by disulfide bond cleavage can simply recombine 38 to regenerate the disulfide bond if the fragments are temporarily held together by noncovalent interactions.…”
Section: Resultsmentioning
confidence: 99%
“… Figure 3 shows the aligned amino acid sequences of various RBL-CRDs. The disulfide bond pairings of RBLs have been determined for Spanish mackerel lectin (SML) by protein sequencing combined with peptide mapping [59] and for SEL24K from Chinook salmon by matrix-assisted laser desorption/ionization (MALDI) mass-spectrometry [132], respectively. Each RBL-CRD had the same disulfide bonding patterns: Cys(1)–Cys(3), Cys(2)–Cys(8), Cys(4)–Cys(7), and Cys(5)-Cys(6) (Figure 3).…”
Section: Structural Characterization Of Rbls: Primary Structures Amentioning
confidence: 99%